THE EFFECTIVENESS OF ROUNDTABLE TECHNIQUE ON STUDENT’S WRITING SKILLS IN DESCRIPTIVE TEXT - Yaqin, M. Ainul; Al Halim, M. Labib (Universitas Islam Lamongan, 2023)
This research aimed to assess the effectiveness of implementing the roundtable technique in enhancing descriptive writing skills among eighth-grade students at SMP Simanjaya Lamongan. The research utilized a pre-experimental one-group pretest-posttest design. Data analysis involved the application of a paired sample t-test to ascertain the presence of a significant effect before and after the intervention. This research included a sample of 30 students from the eighth grade at SMP Simanjaya Lamongan. The findings of the research indicated a notable improvement in students' writing skills when employing the roundtable technique. This was evident in the average scores obtained by students on both the pretest and posttest. The mean score increased from 73.60 during the pretest to 83.03 in the posttest. The researcher then conducted a paired sample t-test to address the research question. The results of the t-test analysis revealed that the p-value (probability value) was below the significance level α (0.00 < 0.05). Consequently, the null hypothesis (Ho), asserting no significant effect of the roundtable technique on students' descriptive writing skills, was rejected. The acceptance of the alternative hypothesis led to the conclusion that the roundtable technique had a significant positive effect on the students' writing skills in producing descriptive texts.